A hybrid seismic isolation system toward more resilient structures: Shaking table experiment and fragility analysis - Rakicevic, Zoran; Bogdanovic, Aleksandra; Noroozinejad Farsangi, Ehsan; Sivandi-Pour, Abbas (Elsevier BV, 2021)
The effectiveness of various vibration control strategies has always been a debate among structural engineers. Seismic base isolation systems and passive dampers are recognized as two of the most economical devices which have passive mechanisms in reducing the structural vibration and responses. To this end, comprehensive biaxial shake table testings have been carried out on a building frame with and without a proposed base isolation system. The proposed device has a novel combined isolation mechanism at the structure's base. By different methods of testing, natural frequencies and viscous damping for the frame model with and without the proposed system were identified. Both structures were intensively tested under various earthquake motions, and various structural responses were recorded. The experimental results indicated that the newly proposed system is very effective in controlling the vibration of building structures and can be used to increase the seismic resilience metrics. As a complementary investigation, the incremental dynamic analysis (IDA) was conducted to develop the seismic fragility curves under both near-field and far-field strong ground motions (SGMs). The fragility estimations indicated that the proposed system has a higher collapse margin ratio (CMR) compared to conventional fixed-base frames.
Keywords: seismic isolation, shaking table testing, fragility analysis, resilient structures